2007
DOI: 10.1128/jcm.00725-07
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Enterocytozoon bieneusi between a Child and Guinea Pigs

Abstract: An unusual Enterocytozoon bieneusi genotype was found in seven guinea pigs and a 2-year-old child in the same household. The genetic uniqueness of the parasite, its wide occurrence in other guinea pigs in the community, and its absence in other children in the community suggest the possibility of zoonotic transmission of the infection to the study child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
96
2
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(104 citation statements)
references
References 24 publications
3
96
2
3
Order By: Relevance
“…1,10 Indeed, at least one case of zoonotically transmitted E. bieneusi infection has been reported. 14 In this study, however, contact with animals was not identified as a risk factor in E. bieneusi infection, although two of three major genotypes found in this study, D and IV, are common in domestic animals and wild mammals in many areas. 5,11 In a previous study conducted in Peru, contact with duck and/or chicken droppings was associated with an increased risk of microsporidiosis.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…1,10 Indeed, at least one case of zoonotically transmitted E. bieneusi infection has been reported. 14 In this study, however, contact with animals was not identified as a risk factor in E. bieneusi infection, although two of three major genotypes found in this study, D and IV, are common in domestic animals and wild mammals in many areas. 5,11 In a previous study conducted in Peru, contact with duck and/or chicken droppings was associated with an increased risk of microsporidiosis.…”
Section: Discussionmentioning
confidence: 64%
“…Bodies of water are known sources of microsporidial infection. 6,14,19 These bodies of water are used as sources for drinking and domestic use, thereby increasing the chances of E. bieneusi infection. Surprisingly, animal contact was not a risk factor for microsporidiosis in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, genotypes CHN7 to CHN10 were likely pig specific. CHN7 and CHN8 were found in monoinfections, while CHN9 and CHN10 coinfected with other genotypes.The ITS sequences of the 10 new genotypes were highly homologous to those of genotypes I, J, K, and G published earlier (3,9,11,14,18) (Fig. 1).…”
mentioning
confidence: 54%
“…The ITS sequences of the 10 new genotypes were highly homologous to those of genotypes I, J, K, and G published earlier (3,9,11,14,18) (Fig. 1).…”
mentioning
confidence: 54%
“…En este sentido, su importancia en salud pública se ha incrementado debido a que los microsporidios que infectan a humanos han sido identificados en fuentes de agua y animales (Desplazes et al, 2000). Dada la enorme variedad de animales infectados por microsporidios, se debe tener en cuenta una posible propagación zoonótica (Cama et al, 2007).…”
Section: Introductionunclassified